DECIPHERING THE ELEMENTS OF MIGRATION IN JASMINE DAYS - Anushya, Dr. K.S. (South Eastern European Journal of Public Health, 2025)
Human migration is as old as human history. Benyamin’s Jasmine Days revolves around the lives of South Asian migrants, recorded through the eyes of the protagonist, Sameera Parvin. The story unfolds around Sameera’s life as a migrant and the emotional and psychological process she undergoes in adapting to the foreign land. This research article titled “Deciphering the Elements of Migration in Jasmine Days” tries to throw light over the elements of migration in the novel Jasmine Days highlighting the impact of Jasmine Revolution in the life of the migrants. It also focusses on the concepts of Hybridity and Acculturation which results due to migration.